PERFORMANCE OF INTEGRATED CONTRACT AND INDEPENDENT BROILER PRODUCTION IN EAST LOMBOK, WEST NUSA TENGGARA - Indarsih, B.; Suryatman, W. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
This study was undertaken to evaluate the performance of vertical integration and independentpoultry producers in East Lombok, West Nusa Tenggara, during the period July to September 2011.Data was collected from a primary field survey of integrated contract and independent producers. Thesample producers were interviewed to collect the required data using a questioner. Supporting data wereobtained from the relevant institution, and poultry association. Thirty integrated contract and fourteenindependent growers were involved to measure farm’s performance with references on numericalperformance (NP) and farmer’ returns. This study indicates that the NP of integrated contract andindependent farms were 315.7 and 317.1, respectively, both was higher than the standard that is 200.Returns for integrated contract farmers were lower than the independent when calculated based on theproduction cycle when this study was undertaken. Integrated contract farmers were attractive to varioustypes of professions, the graduated people of university or college (43.3%) was the most, whilstindependent farmers were dominated by senior high school (50%) with higher experience which wasmore than 20 years.